Pengaruh Konsentrasi Zat Pengatur Tumbuh dan Sumber Bud Chips Terhadap Pertumbuhan Bibit Tebu (Saccharum officinarum) di Pottray - Haris Patar; Asil Barus; Irsal Irsal (Universitas Sumatera Utara, 2015)
This study was conducted in PTPN II Kebun Tanjung Jati, Binjai on June until August 2014. The design of the experiment was randomized block design arranged in factorial with two factors. The first factor was the concentration Rootone F plant growth regulator with 4 levels of each R0 (0 mg/l), R1 (200 mg/l), R2 (400mg/l) and R3 (600 mg/l). The second factor was source of bud chips that origin from 3 parts of stem C1 (top), C2 (middle) dan C3 (bottom). The Parameter observed includes percentage of bud growth ≥ 5%, percentage of bud growth (%), plant height (cm), number leafs (sheet), diameter of stem (mm), volume of root (ml), fresh weight of crown (g), fresh weight of root (g), dry weight of crown (g) and dry weight of root (g).The result of research showed that Rootone F plant growth regulators influential significantly on percentage of bud growth ≥ 5%, diameter of stem 6-10 weeks after planted, volume of root, fresh weight of root, and dry weight of root. Sourced of bud chips influential significantly on percentage of bud growth ≥ 5%, percentage of bud growth 1 and 2 weeks after planted, plant height 2-10 weeks after planted and diameter of stem 2-8 weeks after planted. Interaction between consentration Rootone F plant growth regulator and source of bud chips haven’t the real influences toward all the parameter were observed.Keywords : Plant growth regulators, source of bud chips, sugarcane